Update on Intracerebral Hemorrhage Risk - Vinall, Maria (MD Conference Express, 2014)
Intracerebral hemorrhage (ICH), not related to trauma, is a significant cause of morbidity and mortality. Therapeutic options are few, and none are proven to reduce morbidity or mortality. This article discusses the epidemiology of ICH, use of neuroimaging to establish etiology and to stratify risk for nontraumatic ICH, genetic markers of ICH, as well as the the risk of ICH associated with statin therapy, nonsteroidal anti-inflammatory drugs, alcohol, selective serotonin reuptake inhibitors, and vitamin E.